Duang: The semiotic interpretation and perception of the Bajau-Sama community in Sabah - Halina Sendera Mohd Yakin,; Saidatul Nornis Hj. Mahali, (Universiti Kebangsaan Malaysia, 2008)
This article is to introduce the semiotic interpretation and perception of the Bajau-Sama tradition, specifically on matters pertaining to the traditional funeral customs of the Bajau community in Kota Belud, Sabah. It focuses on the non-verbal communication aspect in the death rituals called the ngeduang ceremony. Ngeduang symbolizes the act of feeding the dead and helping him or her proceed to the new life in the nether world. Ngeduang refers to alms given by the family of the dead to the poor people and the people who attend the feast. The alms is called duang which normally consists of traditional food such as kalas, kuih sinsim, kuih jala’, kuih penjaram, kuih berate, saging randang, kuih wajid, inti’ and also rice and dishes where each will represent something. Besides, the relationship between the explicit and implicit meanings of the duang with the Bajau’s interpretation and perception towards their lives will also be elucidated